Sagot :
Answer:
1. x=3
3x + 4 = 5x - 2
3x - 5x = -2 -4
-2x = -6 (divide both equation by -2)
x=3
2. x=5
6x-10=3x+5
6x-3x= 5+10
6x-3x = 15
3x=15 (divide both equation by 3)
x=5
Answer:
1.) x = 3
2.) x = 5
Step-by-step explanation:
1.) Solutions:
I-subtract ang sa magkabilang bahagi ng equation
3 + 4 = 5 − 2
3 + 4 − 4 = 5 − 2 − 4
Pasimplehin
3 = 5 − 6
I-subtract ang sa magkabilang bahagi ng equation
3 = 5x − 6
3 − 5 = 5 − 6 − 5
Pasimplehin
− 2 = − 6
I-divide ang magkabilang bahagi ng equation sa parehong term
− 2 = − 6
− 2 = − 6
= − 2 − 2
Pasimplehin
= 3
__________________________________________________________
2.) Solutions:
Simplifying:
6x + 10 = 3x + -5
Reorder the terms:
10 + 6x = 3x + -5
Reorder the terms:
10 + 6x = -5 + 3x
Solving
10 + 6x = -5 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
10 + 6x + -3x = -5 + 3x + -3x
Combine like terms: 6x + -3x = 3x
10 + 3x = -5 + 3x + -3x
Combine like terms: 3x + -3x = 0
10 + 3x = -5 + 0
10 + 3x = -5
Add '-10' to each side of the equation.
10 + -10 + 3x = -5 + -10
Combine like terms: 10 + -10 = 0
0 + 3x = -5 + -10
3x = -5 + -10
Combine like terms: -5 + -10 = -15
3x = -15
Divide each side by '3'.
x = -5
Simplifying
x = -5
Hope it helps